Labor market dynamics in a highly competitive industry - Francesco van Principe; Jan C. Ours (Tinbergen Institute, 2025)
We study labor market dynamics of workers in a highly competitive industry, focusing on the relationship between workers' age, wages, and productivity. Our analysis uncovers an inverse U-shaped relationship. While some wage adjustments occur within the current firm, job mobility plays a crucial role in shaping wage trajectories. There is assortative matching with highly productive workers moving to highly productive firms, while less productive workers gravitate towards less productive firms. Our findings suggest that both in-firm wage progression and wage growth via job mobility contribute to a close alignment between wages and productivity throughout workers' careers.
Keywords: J31; J62; Z22; 330; Age-wage profile; productivity; job mobility